2011
DOI: 10.1074/jbc.m110.200790
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of Chondroitin Sulfate to Regulate Hyaluronan Binding by Receptor CD44 in Inflammatory and Interleukin 4-activated Macrophages

Abstract: CD44 is a cell surface receptor for the extracellular matrix glycosaminoglycan hyaluronan and is involved in processes ranging from leukocyte recruitment to wound healing. In the immune system, the binding of hyaluronan to CD44 is tightly regulated, and exposure of human peripheral blood monocytes to inflammatory stimuli increases CD44 expression and induces hyaluronan binding. Here we sought to understand how mouse macrophages regulate hyaluronan binding upon inflammatory and anti-inflammatory stimuli. Mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 65 publications
2
54
0
Order By: Relevance
“…4). The clustered particles formed agglomerations of gold signals of 100-300 nm in size in the untreated cells ( Johnson and others have intensively investigated the regulation of CD44 function, and shown that post-translational modifications to CD44 are implicated in modulating its HA-binding ability (Katoh et al, 1995;English et al, 1998;Skelton et al, 1998;Levesque and Haynes, 1999;Ruffell et al, 2011;Maiti et al, 1998;Brown et al, 2001). Under the conditions described here, however, the involvement of post-translational modifications may not matter, since the HA-binding ability of CD44 rose within 30 minutes (Fig.…”
Section: Mbcd Upregulates the Ha-binding Ability Of Cd44mentioning
confidence: 99%
See 1 more Smart Citation
“…4). The clustered particles formed agglomerations of gold signals of 100-300 nm in size in the untreated cells ( Johnson and others have intensively investigated the regulation of CD44 function, and shown that post-translational modifications to CD44 are implicated in modulating its HA-binding ability (Katoh et al, 1995;English et al, 1998;Skelton et al, 1998;Levesque and Haynes, 1999;Ruffell et al, 2011;Maiti et al, 1998;Brown et al, 2001). Under the conditions described here, however, the involvement of post-translational modifications may not matter, since the HA-binding ability of CD44 rose within 30 minutes (Fig.…”
Section: Mbcd Upregulates the Ha-binding Ability Of Cd44mentioning
confidence: 99%
“…In fact, CD44 on resting T cells does not bind HA, but can be induced to bind it upon T cell activation with antigen via the T cell receptor (TCR) (DeGrendele et al, 1997;Lesley et al, 1994;Ariel et al, 2000;Firan et al, 2006;Maeshima et al, 2011). Studies report that various posttranslational modifications on CD44, including glycosylation (Katoh et al, 1995;English et al, 1998;Skelton et al, 1998), chondroitin sulfate addition (Levesque and Haynes, 1999;Ruffell et al, 2011), and sulfation (Maiti et al, 1998;Brown et al, 2001), affect its HA-binding ability. However, the membrane-based regulation of CD44's HA-binding ability has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Specific environments and the cytokine milieu likely contribute to this phenotypic, and possibly functional, heterogeneity. For example, the addition of IL-4 to M-CSF-induced bone marrow-derived macrophages (BMDMs) upregulates CD11c and downregulates F4/80 (10). Whereas peritoneal and splenic red pulp macrophages are positive for F4/80 and CD11b, alveolar macrophages express low levels of these classical macrophage markers and high levels of CD11c (6,11).…”
mentioning
confidence: 99%
“…CD44 is the major cell-surface receptor for HA on immune cells, but not all CD44-expressing cells bind HA (29,30). On human monocytes, CD44 can be induced to bind HA by various inflammatory cytokines including GM-CSF, IL-1a and IL-1b, and TNF-a (25,31), and M-CSF-derived BMDMs only bind HA after they are stimulated with M1 or M2 polarizing agents (10). However, the functional significance of this induced binding remains enigmatic.…”
mentioning
confidence: 99%
See 1 more Smart Citation